Sputum Smear Positive Pulmonary Tuberculosis Diagnostic Dropout Rate in Public Health Facilities, Addis Ababa, Ethiopia - Desalegn, Daniel Melese; Kitila, Kumera Terfa; Taddese, Boja Dufera; Hailu, Tinsae Kidanemariam; Dinku, Tariku Takle; Asferie, Kassahun Demisse; Balcha, Hanna Mekonnen; Gebeyehu, Chalachew Sisay; Medhin, Girmay (Pulmonary Medicine, 2019)
Background. Prolonged laboratory diagnostic process of tuberculosis can lead to failure to complete the diagnosis and increase dropout rate of smear positive pulmonary tuberculosis (PTB) cases. This implies such dropout patients without completing diagnosis are critical as infected individuals remain untreated in the community, providing more opportunities for transmission of the disease and adversely affecting the epidemic. The aim of this research is to determine the level of smear positive PTB diagnosis dropout rate of spot-morning-spot sputum microscopy diagnosis method in public health facilities, in Addis Ababa, Ethiopia. Methods. Retrospective review of patient documents in 13 public health facilities’ TB laboratory in Addis Ababa was conducted from October 2011 to March 2016. Data was computerized using Epi-info software and analysed using SPSS version 20.0 software. Descriptive numerical summaries were used to present the findings. Association between the dropout rate and demographic variables was assessed by Chi-square (X2). Bivariate model using Odds Ratio (OR) with a 95% Confidence Interval (CI) was calculated. P-Value less than 0.05 was taken as statistically significant. Results. Of 41,884 presumptive TB patients registered during the 53 months for laboratory investigation, 5.9% were positive for the first spot sputum smear microscopy. Among these positive cases, 142 (5.8%) and 298 (12.1%) did not come back to the laboratory to submitted early morning and second spot sputum specimens, respectively. The diagnostic dropout for morning sputum specimen in hospitals was 5.6% (58/1039) and in health centres was 5.9% (84/1424). However, higher proportion of dropout for second spot sputum specimen in hospitals was 16.4% (170/1039), compared to the health centres, 8.9% (128/1424). Diagnostic dropout of sputum smear microscopy had no significant association with sociodemographic variable (P value >0.05), while it had significant association with facility type (P value <0.05). Conclusion. In this study smear positive pulmonary tuberculosis diagnostic dropout rate was high compared to WHO reported for the new strategy shift implying the importance of shifting to same-day approach. Hence, shifting from conventional to same day is crucial to minimize the TB diagnostic dropout rate in the study area and other similar settings. Further research is needed/recommended in the local setting to compare the yield and dropout rates between same-day and conventional sputum smear microscopy approach.